2020
DOI: 10.1002/rra.3744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obstacles and flow velocity on locomotory behavior in juvenile, silver carp,Hypophthalmichthys molitrix

Abstract: We currently have only a minimal understanding of energy‐saving strategies of fish in unsteady flows. In this study, we found that obstacle shape can affect swimming ability of fish: our results suggested that a half cylinder improved critical swimming speed of silver carp (Hypophthalmichthys molitrix) compared with swimming downstream of a full cylinder, square tube or for free‐flow conditions. We also discovered how silver carp alter their locomotory behavior in response to turbulent flow caused by varying f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Within the models, all fixed effects are categorical variables with the following levels: BL, small fish (1) and large fish (2); CD, free stream (1), 1.9 cm cylinder (2), 2.5 cm cylinder (3), 3.2 cm cylinder (4) and 5.0 cm cylinder (5); MBT, non-FRB swimming (1) and FRB (2). Previous study (Ke et al, 2021) has shown that silver carp's motions resembled free-stream swimming behaviour at low flow velocity (less than <3 BL/s). To better understand how U rcrit is affected by FRB, we selected intermediate to high velocity (40-90 cm s -1 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Within the models, all fixed effects are categorical variables with the following levels: BL, small fish (1) and large fish (2); CD, free stream (1), 1.9 cm cylinder (2), 2.5 cm cylinder (3), 3.2 cm cylinder (4) and 5.0 cm cylinder (5); MBT, non-FRB swimming (1) and FRB (2). Previous study (Ke et al, 2021) has shown that silver carp's motions resembled free-stream swimming behaviour at low flow velocity (less than <3 BL/s). To better understand how U rcrit is affected by FRB, we selected intermediate to high velocity (40-90 cm s -1 ).…”
Section: Discussionmentioning
confidence: 84%
“…Kinematics parameters such as tail-beat frequency and amplitude were calculated from 10 midlines corresponding to a complete tail-beat cycle. Tail-beat frequency refers to the number of tail beat cycles recorded per second, whereas a beat cycle refers to a single bout of movement that begins when a fish tail is at its highest point and ends when it returns to that point (Ke et al, 2021). Tail-beat amplitude refers to half of the peak-to-peak amplitude recorded in the tail beat cycle.…”
Section: Quantifying Locomotory Behaviourmentioning
confidence: 99%
See 1 more Smart Citation